Comparative effects of 3,5-diiodo-L-thyronine and 3,5,3’-triiodo-L-thyronine on mitochondrial damage and cGAS/STING-driven inflammation in liver of hypothyroid rats - Giacco, Antonia; Petito, Giuseppe; Silvestri, Elena; Scopigno, Nicla; Vigliotti, Michela; Mercurio, Giovanna; de Lange, Pieter; Lombardi, Assunta; Moreno, Maria; Goglia, Fernando; Lanni, Antonia; Senese, Rosalba; et al. (Frontiers in Endocrinology, 2024)
Maintaining a well-functioning mitochondrial network through the mitochondria quality control (MQC) mechanisms, including biogenesis, dynamics and mitophagy, is crucial for overall health. Mitochondrial dysfunction caused by oxidative stress and further exacerbated by impaired quality control can trigger inflammation through the release of the damage-associated molecular patterns (mtDAMPs). mtDAMPs act by stimulating the cyclic GMP-AMP synthase (cGAS) stimulator of interferon genes (STING) pathway. Recently, aberrant signalling of the cGAS-STING axis has been recognised to be closely associated with several sterile inflammatory diseases (e.g. non-alcoholic fatty liver disease, obesity). This may fit the pathophysiology of hypothyroidism, an endocrine disorder characterised by the reduction of thyroid hormone production associated with impaired metabolic fluxes, oxidative balance and inflammatory status. Both 3,5,3'-triiodo-L-tyronine (T3) and its derivative 3,5-diiodo-L-thyronine (3,5-T2), are known to mitigate processes targeting mitochondria, albeit the underlying mechanisms are not yet fully understood. Therefore, we used a chemically induced hypothyroidism rat model to investigate the effect of 3,5-T2 or T3 administration on inflammation-related factors (inflammatory cytokines, hepatic cGAS-STING pathway), oxidative stress, antioxidant defence enzymes, mitochondrial DNA (mtDNA) damage, release and repair, and the MQC system in the liver. Hypothyroid rats showed: i) increased oxidative stress, ii) accumulation of mtDNA damage, iii) high levels of circulating cytokines, iv) hepatic activation of cGAS-STING pathways and v) impairment of MQC mechanisms and autophagy. Both iodothyronines restored oxidative balance by enhancing antioxidant defense, preventing mtDNA damage through the activation of mtDNA repair mechanisms (OGG1, APE1, and POL) and promoting autophagy progression. Concerning MQC, both iodothyronines stimulated mitophagy and dynamics, with 3,5-T2 activating fusion and T3 modulating both fusion and fission processes. Moreover, only T3 enhanced mitochondrial biogenesis. Notably, 3,5-T2, but not T3, reversed the hypothyroidisminduced activation of the cGAS-STING inflammatory cascade. In addition, it is noteworthy that 3,5-T2 seems more effective than T3 in reducing circulating pro-inflammatory cytokines IL-6 and IL-1B and in stimulating the release of IL-10, a known anti-inflammatory cytokine. These findings reveal novel molecular mechanisms of hepatic signalling pathways involved in hypothyroidism, which could be targeted by natural iodothyronines, particularly 3,5-T2, paving the way for the development of new treatment strategies for inflammatory diseases.